The Influence of Work Motivation, Work Culture, Work Discipline, and Work Environment on Employee Performance with Work Ethic as an Intervening Variable at PT. Ultiface - Ning Kholishotul Ilmi; Khamdan Rifa'i; Nurul Setianingrum (Dinasti Publisher, 2024)
This study aims to investigate the influence of work motivation, work culture, work discipline, and work environment on employee performance at PT. Ultiface, with work ethic as the mediating variable. A quantitative method with an associative approach was employed, with a population of 136 employees from PT. Ultiface and a saturated sample of 121 respondents. Data analysis was conducted using Partial Least Square (PLS) version 3.0. The research findings indicate that work motivation (t = 2.757, p = 0.006), work environment (t = 4.765, p = 0.000), and work ethic (t = 4.261, p = 0.000) have a significant influence on employee performance, while work culture (t = 1.825, p = 0.069), work discipline (t = 1.245, p = 0.214), and the intervention of work ethic through work motivation (t = 2.776, p = 0.006) are significant. However, the intervention of work ethic through work culture (t = 0.805, p = 0.421), work discipline (t = 0.121, p = 0.904), and work environment (t = 1.855, p = 0.064) does not show a significant influence on employee performance. This study is expected to provide useful insights for the management of PT. Ultiface in enhancing employee performance through effective management of these factors.